APLIKASI ALAT UKUR PARTIKULAT DAN SUHU BERBASIS IOT - Syamsudduha Syahrorini; Dwi Hadidjaja (Universitas Stikubank, 2020)
Human daily life depends on air, so air quality needs to be protected especially against pollution. Decreasing air quality due to dust pollution can result in ARI. Makes it easier to measure ambient air and air temperature using internet-based technology. Designing internet-based dust and temperature measuring devices using the gp2y1010au0f type dust sensor, and DHS11 sensor as a temperature sensor, amplifier circuit, NodemCU microcontroller, and LCD (Liquid Crystal Display). The measurement application is carried out at the location of the PT. Djabus Tunas Utama Ngoro Mojokerto East Java at 10 sampling points around the mixing tube. The measurement results show the concentration carried by ambient air quality standards when the engine stops, so it is safe for employees. When the machine is mixing and the machine is not mixing (ordinary conditions) the concentration of particulates and the temperature exceeds the ambient air quality standard, for that all employees are required to use PPE.